Validation a Model of Learning Facilitators Club Related to Professional Training Development in Employees of Hormozgan Education Department - Ahad Ameri; Mohammadnoor Rahmani; Leila Khajehpour (Iranian Journal of Educational Research)
Objective: Facilitating learning serves as one of the mechanisms for organizational development within various organizations. With this in mind, the present study aimed to validate the model of the learning facilitators' club in relation to the professional training and development of employees within the Education Department of Hormozgan province. Methods: The research approach employed was descriptive, and the statistical population consisted of education employees from Hormozgan province. A sample of 30 individuals was selected using the accessible sampling method. Data was collected through a researcher-made questionnaire, which was deemed valid by experts. Data analysis was conducted using the one sample T test. Results: The findings revealed that the model of the club, pertaining to professional training and development of learning facilitators, was significantly approved and agreed upon by experts and scholars. Based on the findings, the model showcased significant relevance to the research subject, applicability, relationships between its elements, comprehensiveness, comprehensibility, innovation, and widespread use. Conclusions: Therefore, according to experts, the model of the Club of Learning Facilitators, which focuses on the professional training and development of the Education Department in Hormozgan Province, attains a high level of favorability.